On lacunary statistical convergence of order ? in probability - Isik, Mahmut; Et, Kubra Elif (Amer Inst Physics, 2015)
In this study, we examine the concepts of lacunary statistical convergence of order a in probability and N-theta-convergence of order a in probability. We give some relations connected to these concepts.
International Conference on Advancements in Mathematical Sciences (AMS) -- NOV 05-07, 2015 -- Antalya, TURKEY
Keywords: Statistical convergence of order a in probability; Cesaro summability of order a in probability; Lacunary statistical convergence